Peran Orangtua Dalam Pembentukan Karakter Anak Era Digital Di POS PAUD Permata Bunda Sidoarjo - Purnama Sari, Tungga (Jurnal Dremi (Demi Pengabdi Masyarakat), 2025)
The development of digital technology presents new challenges in shaping children’s character, where parents’ role as digital role models is crucial. Many parents struggle to guide their children in using gadgets and social media, increasing the risk of cyberbullying, gadget addiction, and unethical behavior. This community service activity was conducted as a participatory-educational parenting seminar combining counseling, practical digital parenting training, and group discussions. The target participants were approximately 20 parents of early childhood children. The results showed a significant improvement in parents’ understanding of digital literacy, their role as digital role models, screen time management, effective communication, and application of digital etiquette. Parents recognized the importance of active involvement in digital parenting and fostering quality family interactions. These findings indicate that digital literacy-based parenting seminars are effective in supporting children’s character development in the digital era and can be replicated to strengthen character education in other communities.